Conceptualizing Power in Dynamics of Securitization Beyond State and International System - Langenohl, Andreas; Kreide, Regina (2019)
This volume addresses the 'question of power' in current constructivist securitisation studies. How can power relations that affect security and insecurity be analysed from both a transdisciplinary and historical point of view? The volume brings together contributions from history, art history, political science, sociology, cultural anthropology and law in order to determine the role of conceptions of power in securitisation studies, which has tended to be dealt with implicitly thus far. Using conceptual theoretical essays and historical case studies that cover the period from the 16th to the 21st century, this book portrays the dominant paradigms of critical security studies, which mostly stem from the field of international relations and see the state as a major focal point in securitisation, in a new light.